Ph value, temperature, conductivity, and dissolved oxygen in water from seven selected rivers at Ranau Sabah - Rohana Tair; M.H. Abdullah; H. Juahir; S.A. Rahim; Baba Musta (Faculty of Science and Natural Resources, 2020)
Monitoring water quality in river water is the major research at this decade due to the concerns of the water resources and sustainability. Ranau has known as heritage area that located at high altitude area (Kinabalu mountain) and has an excellent tourism opportunity in Sabah. Unfortunately, the biggest high-altitude lake caused by ex-copper mining activity also located behind. The lake contains of acid mine drainage water (AMD). Naturally, water flows from upstream to the downstream. Monitoring the river water at the downstream of Ranau area is main concerns in this study. So, the purposed of this study is to determine the water quality parameters (pH value, temperature, conductivity and dissolved oxygen (DO)) at seven selected rivers located at downstream which were Lohan, Bongkud, Panginatan, Langganan, Mantakungan, Kilimu and Mongkodou Rivers, respectively. The measurement was done by using mutlimeters YSI ProDSS digital sampling system. The concentrations of parameters were in range of 7.38<7.88<24.67<0.25<7.85